Surface states in optical spectra of two-dimensional photonic crystals with various surface terminations - PEROVA, TANIA (My University, 2012)
Reflection and transmission spectra of two-dimensional photonic crystal slabs, fabricated by photoelectrochemical etching of deep macropores and trenches in Si, are investigated theoretically and experimentally. It is shown that the presence of an unstructured silicon interfacial layer between the air and the photonic crystal structure can give rise to surface (Tamm) states within the TE and TM photonic stop bands. In the presence of roughness of inner surfaces of air pores, the surface states show up as dips within the stop bands in the reflection spectrum. The calculated electromagnetic near-field distribution demonstrates the vortices between the upper pores at the frequency of the surface mode. The experimental reflection and transmission spectra are in a good agreement with theoretical calculations performed by the Fourier modal method in the scattering matrix form.
PUBLISHED
Keywords: photonic crystals; Nanoscience & Materials